Quantification of Training Load and Training Response for Improving Athletic Performance. Issue 5 (October 2017) - Campbell, Bill I.; Bove, Daniel; Ward, Patrick; Vargas, Andres; Dolan, Jeff
Abstract : ABSTRACT: ONE IMPORTANT RESPONSIBILITY OF A STRENGTH AND CONDITIONING COACH IS THE DEVELOPMENT OF A TRAINING PROGRAM THAT ENHANCES PHYSIOLOGICAL QUALITIES, WITH THE GOAL OF IMPROVING ATHLETIC PERFORMANCE. TO ACHIEVE THIS GOAL, COACHES DESIGN TRAINING PROGRAMS THAT SUCCESSFULLY APPROPRIATE AND MANAGE TRAINING VOLUME AND INTENSITY DURING THE ATHLETE'S OFFSEASON, PRESEASON, AND IN-SEASON PERIODS. BY QUANTIFYING TRAINING LOADS AND RESPONSES, COACHES CAN BETTER PRESCRIBE TRAINING STIMULI WHILE ALSO MANAGING STRESS LEVELS. ATHLETE-MONITORING STRATEGIES PROVIDE A WAY FOR STRENGTH COACHES TO GATHER USEFUL INFORMATION REGARDING TRAINING DEMANDS AND ATHLETE FATIGUE.